2020
DOI: 10.1027/0227-5910/a000594
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support and Mental Health After Suicide Loss

Abstract: Abstract. Background: Despite great need, social support is limited after suicide loss, which could contribute to worse mental health outcomes including increased suicidality among suicide loss survivors. Aims: To examine the associations between perceived social support, grief difficulties, depressive symptoms, suicidality, and personal growth among 195 suicide loss survivors. Method: The associations between perceived social support, grief difficulties, depressive symptoms, suicidality, and personal growth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 33 publications
1
48
0
2
Order By: Relevance
“…There was consistent evidence that social support influences positive wellbeing, with three separate studies [30,39,44] measuring personal growth, stress-related growth and resilience. A study [44] with a low risk of bias found that increased personal growth was cross-sectionally associated with increased social support, and a study [39] with a medium risk of bias found that increased stressrelated growth was cross-sectionally associated with increased social support. Social support mediated the association between traumatic stress and resilience in a study [30] with a medium risk of bias.…”
Section: Other Psychological Wellbeing Outcomes (Eight Studies)mentioning
confidence: 71%
See 4 more Smart Citations
“…There was consistent evidence that social support influences positive wellbeing, with three separate studies [30,39,44] measuring personal growth, stress-related growth and resilience. A study [44] with a low risk of bias found that increased personal growth was cross-sectionally associated with increased social support, and a study [39] with a medium risk of bias found that increased stressrelated growth was cross-sectionally associated with increased social support. Social support mediated the association between traumatic stress and resilience in a study [30] with a medium risk of bias.…”
Section: Other Psychological Wellbeing Outcomes (Eight Studies)mentioning
confidence: 71%
“…The similar constructs of grief, mourning, and extent of grief difficulties, were each significantly crosssectionally associated with social support in two separate exploratory studies [36,44], both with a low risk of bias.…”
Section: Other Psychological Wellbeing Outcomes (Eight Studies)mentioning
confidence: 89%
See 3 more Smart Citations